Answer:
5x^2 - 11x = 1
This is now in standard form, where a = 5, b = -11, and c = 1.
Step-by-step explanation:
To rewrite the equation 11x - 5x^2 + 7 = 6 in standard form, we need to rearrange the terms so that the polynomial is in descending order of degree, with no missing terms. The standard form of a quadratic equation is ax^2 + bx + c = 0, where a, b, and c are constants.
So, let's start by moving the constant term to the right-hand side of the equation:
11x - 5x^2 = 6 - 7
11x - 5x^2 = -1
Next, we can multiply both sides of the equation by -1 to make the coefficient of the x^2 term positive:
5x^2 - 11x = 1
This is now in standard form, where a = 5, b = -11, and c = 1.
A. 82
B. 63
C. 81
D. 83
Answer: 15/12
Step-by-step explanation:
-2- 13 =-15
4- -8 = 12
Remember the formula y2-y1. Divided by x2 - x1
Answer:
C
Step-by-step explanation:
The weight of the weight lighting bar = the initial value/y-intercept (b) = 45
Amount of weight = x
Total amount of weight = y
The rate of change (m) = 1
Thus to write the function that models this situation, substitute m = 1, and b = 45 into y = mx + b
Thus:
y = (1)x + 45
y = x + 45
The correct option is c